GC-MS Analysis of the Essential Oil and Petroleum Ether Extract of Different Regions of Korean Ginger (Zingiber officinale) and Antioxidant Activity - Chung, Ill-Min; Praveen, Nagella; Kim, Sun-Jin; Ahmad, Ateeque (Asian Journal of Chemistry, 2011)
The composition of the rhizomes of Zingiber officinale essential oil and petroleum ether extract of two different regions of Korea namely Busan and Youngam were examined by gas chromatographic- mass spectroscopic analysis (GC-MS). The essential oil yield (mL/100 g dry weight) were 0.40 (Busan region) and 0.60 % (Youngam region), respectively. Thirty seven and thirty five compounds comprising 98.72 and 80.34 % of the total peak area were identified in the Busan and Youngam regions, respectively. The common major components of essentials oils in these two regions are camphene (18.32, 14.08 %), a-phellandrene (8.83, 5.21 %), bicyclo[3.1.0]hexan-2-ol 2-methyl-5-(1-methyl ethyl)-1a,2a,5a- (2.10, 12.68 %), zingiberene (6.68, 11.15 %), zingiberenol (1.71, 1.05 %), linalool (4.11, 2.25 %), Z-citral (1.81, 3.73 %), a- farnesene (6.72, 2.98), geraniol (7.61, 3.26 %). Forty compounds each comprising 100.00, 99.99 % of the total peak area were identified in Busan and Youngam regions varieties of ginger, respectively of petroleum ether extract. The common major constituents are sabinene (5.91, 2.30 %), borneol (3.26, 2.97 %), 3-cyclohexene-1-methanol a,a-trimethyl (2.50, 2.54 %), geraniol (6.35, 7.98 %), 2,6-octadienal 3,7-dimethyl (12.63, 13.19 %), 2,6-octadien-1-ol 3,7- dimethyl acetate (6.94, 8.68 %), bicyclo[3.1.1]hept-2-ene 2,6-dimethyl-6-(4-methyl-3-petenyl)- (23.18, 18.56 %), naphthalene 1,2,4a,5,6,8a-hexahydro-4,7-dimethyl-1-(1-methylethyl)-(8.10, 9.73 %), a-sesquiphellandrene (10.11, 12.48 %), nerolidol (1.46, 2.74 %). The essential oil and hexane extract from two varieties of ginger was investigated for scavenging of the diphenylpicrylhydrazyl (DPPH) radical activity and the results demonstrate that the hexane extract is more potential than the essential oil from the ginger as a natural antioxidant and thus inhibit undesired oxidation process.